The Relative Value of Measures of Omega-3 Index, Perceived Stress, Cortisol and Sleep Time in Identifying Depression Among a Cohort of Australian Adolescents (International Journal of Child Health and Nutrition, 2015)
Objective: To assess the relative prognostic value of 11 variables including, omega-3, perceived stress, cortisol and sleep duration, in predicting adolescent depression.Design, Setting and Participants: A cross-sectional study of 444 healthy adolescents aged 16-18 years, from 10 schools within the Northern Sydney and Central Coast regions of New South Wales, Australia. Participants provided blood and saliva samples and completed questionnaires. Statistical classification methods were used to model the relationships between the predictors and depression.Main Outcome Measures: relative predictive value of each variable in correctly classifying depression.Results: 6% of boys and 9% of girls were categorised as experiencing severe to extremely severe depression. 4% of boys and 10% of girls were categorised as experiencing severe to extremely severe stress. The mean AM:PM cortisol for boys, 22±101, was higher than that of girls, 11±10. The average omega-3 index for boys, 10.5±3.7, was also higher than that of girls, 7.7±2.6. The average sleep duration of 7.8±1.1 hrs showed no gender differences.The best classification model identified perceived stress as the most significant predictor of depression followed by BMI and omega-3 index. Cortisol ratio was a significant discriminator for boys but not girls. When stress was excluded, shorter sleep duration became a significant discriminator in both boys and girls with waist to hip ratio providing further discrimination in girls only.Conclusion: The strongest predictor of depression in adolescents was perceived stress followed by higher BMI and lower omega-3 levels. These findings provide a rational basis for establishing program priorities for the prevention and treatment of adolescent depression.